Orthogonal MET analysis in a population‐representative stage II–III colon cancer cohort: prognostic and potential therapeutic implications. Issue 12 (1st November 2021) - Craig, Stephanie G.; Mende, Svenja; Humphries, Matthew P.; Bingham, Victoria; Viratham Pulsawatdi, Amélie; Loughrey, Maurice B.; Coleman, Helen G.; McQuaid, Stephen; Wilson, Richard H.; Van Schaeybroeck, Sandra; James, Jacqueline A.; Salto‐Tellez, Manuel
Abstract : Clinical trials for MET inhibitors have demonstrated limited success for their use in colon cancer (CC). However, clinical efficacy may be obscured by a lack of standardisation in MET assessment for patient stratification. In this study, we aimed to determine the molecular context in which MET is deregulated in CC using a series of genomic and proteomic tests to define MET expression and identify patient subgroups that should be considered in future studies with MET ‐targeted agents. To this aim, orthogonal expression analysis of MET was conducted in a population‐representative cohort of stage II/III CC patients ( n = 240) diagnosed in Northern Ireland from 2004 to 2008. Targeted sequencing was used to determine the relative incidence of MET R970C and MET T992I mutations within the cohort. MET amplification was assessed using dual‐colour dual‐hapten brightfield in situ hybridisation (DDISH). Expression of transcribed MET and c‐MET protein within the cohort was assessed using digital image analysis on MET RNA in situ hybridisation (ISH) and c‐MET immunohistochemistry (IHC) stained slides. We found that less than 2% of the stage II/III CC patient population assessed demonstrated a genetic MET aberration. Determination of a high MET RNA‐ISH/low c‐MET IHC protein subgroup was found to be associated with poor 5‐year cancer‐specific outcomes compared to patients with concordant MET RNA‐ISH and c‐MET IHC protein expression (HR 2.12 [95%CI: 1.27–3.68]). The MET RNA‐ISH/c‐MET IHC protein biomarker paradigm identified in this study demonstrates that subtyping of MET expression may be required to identify MET ‐addicted malignancies in CC patients who will truly benefit from MET inhibition. Abstract : A population representative study looking at the molecular context in which MET is deregulated in colon cancer using a series of genomic and proteomic tests. This study demonstrates the limited number of genetic MET aberrations present in a Northern Irish colon cancer cohort and identifies a cancer‐specific poor prognosis MET RNA/c‐MET protein subgroup that may be amenable to targeted therapy.